Using INTERSPIA to Explore the Dynamics of Protein‐Protein Interactions Among Multiple Species. Issue 1 (21st November 2019) - Kwon, Daehong; Lee, Daehwan; Kim, Juyeon; Lee, Jongin; Sim, Mikang; Kim, Jaebum
Abstract: INTER‐Species Protein Interaction Analysis (INTERSPIA) is a web application for identifying diverse patterns of protein‐protein interactions (PPIs) in different species. Given a set of proteins of interest to the user, INTERSPIA first discovers additional proteins that are functionally associated with the input proteins as well as different or common patterns of PPIs among the proteins in multiple species through a server‐side pipeline. Second, it visualizes the dynamics of PPIs in multiple species via an easy‐to‐use web interface. This article contains a basic protocol describing how to visualize diverse patterns of PPIs of input proteins in multiple species, and how to use them for functional analysis in the web interface. INTERSPIA is freely available at http://bioinfo.konkuk.ac.kr/INTERSPIA/ . © 2019 by John Wiley & Sons, Inc. Basic Protocol : Running INTERSPIA using a list of input proteins